2015
DOI: 10.1097/sla.0000000000000716
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the World Health Organization Checklist on Patient Outcomes

Abstract: Implementation of the WHO SSC was associated with robust reduction in morbidity and length of in-hospital stay and some reduction in mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
220
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 244 publications
(237 citation statements)
references
References 37 publications
8
220
3
6
Order By: Relevance
“…[2,[5][6][7][8] The overall complication rates in our study were lower than those reported by others. [4,5,7] This may be because previous studies were done in tertiary, central or specialised teaching hospitals on highrisk patients, and we specifically excluded such hospitals. Most women in our study were of low preoperative risk.…”
Section: Other Findingscontrasting
confidence: 54%
See 2 more Smart Citations
“…[2,[5][6][7][8] The overall complication rates in our study were lower than those reported by others. [4,5,7] This may be because previous studies were done in tertiary, central or specialised teaching hospitals on highrisk patients, and we specifically excluded such hospitals. Most women in our study were of low preoperative risk.…”
Section: Other Findingscontrasting
confidence: 54%
“…compli cation rates we observed in hospitals where the MSSCL was being well implemented were slightly higher than those found in a large study by Urbach et al [2] The significant reduction in overall complication rates in the intervention hospitals in the current study is supported by other studies, [4,7] but this has not been consistently demonstrated. [2,17] Infection rates in the intervention arm of our study were lower than reported in the literature, with De Vries et al [5] reporting an infection rate of 4.8% before and 3.3% after intervention, compared with 6.8% before and 6.3% after intervention in the control arm of our study.…”
Section: Researchcontrasting
confidence: 52%
See 1 more Smart Citation
“…Checklists and guidelines designed for these scenarios can be grouped together under the term 'cognitive aids'. Such aids appear to be beneficial; there is evidence demonstrating reduced mortality with checklists for central venous access on intensive care units [1] and surgical safety checklists in operating theatres [2][3][4]. The probability of demonstrating that cognitive aids reduce morbidity or mortality in emergency care is limited by the rarity of these events; however, in the field of anaesthesia and surgery, checklists have been shown to improve the management of simulated intra-operative crises [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in mortality ranging from 18 to 47% has been shown in different studies employing wide scale hospital use of surgical checklists [12,13]. A recent randomized trial assessing the use of surgical checklists demonstrated that patient morbidity resulting from surgical complications is also reduced, with a relative risk reduction of 0.42 (95% confidence interval, 0.33-0.50) [14]. Despite these recognized studies and CMS mandate, the self-reported rate of utilization of surgical checklists by ophthalmologists was low in our survey, with 36% of the respondents never using a surgical checklist and 24% not conducting an implant timeout.…”
Section: Discussionmentioning
confidence: 99%